Preparation of an Operational Curriculum Based on Local Wisdom for Students in PAUD - Sumarni, Sumarni; Rusmayadi, Rusmayadi; Musi, Muhammad Akil; Halik, Abdul (PT. Riset Press International, 2025)
Local wisdom as a cultural heritage owned by a community, including traditions, values, customs, and local knowledge that has been passed down from generation to generation. Within the scope of PAUD, local wisdom has great potential to become an integral part of the learning process, enrich children's learning experiences, and strengthen their cultural identity. This research aims to find out the preparation of an operational curriculum based on local wisdom and to find out the challenges faced in the preparation of an operational curriculum based on local wisdom in PAUD. The research method used is descriptive qualitative research with a descriptive approach. The results of the study show that the process of preparing the curriculum through systematic stages involves analyzing needs, formulating goals, determining the content and structure of the program, and developing learning strategies that integrate elements of local wisdom. Collaboration between the school, community leaders, and parents of students is the key in identifying and integrating relevant local wisdom in the curriculum. Conclusions and suggestions in this study are periodic training to improve teachers' understanding and skills in integrating local wisdom into learning. The Education Office should provide guidance and training for schools in developing an operational curriculum based on local wisdom.